The Influence of Oversight, Anti-Fraud Strategies, and Sharia Compliance Audits on Preventive Fraud Efforts (Issuers in the Islamic Financial Institutions Sector on the Indonesia Stock Exchange for the Period 2019-2023) - Muhammad Maulana Hafizh; Tutty Nuryati; Tri Yulaeli; Beti Nurbaiti; Endah Prawesti Ningrum (Research Trend in Technology and Management, 2025)
This study analyzes the effect of Supervision, Anti-fraud Strategy, and Sharia Compliance Audit on Preventive Fraud Efforts. The research population includes issuers in the Islamic Financial Institutions sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. By using purposive sampling technique, 42 samples were obtained consisting of 8 issuers for six years. Secondary data is obtained from financial reports, sustainability reports, corporate governance reports, and annual reports of issuers. Analysis using Descriptive Statistical techniques, Classical Assumption Test, Hypothesis Test, and Determination Coefficient Test with the help of the Eviews 13 application. The results showed that Supervision has no effect on Preventive Fraud Efforts. Conversely, the Anti-fraud Strategy, and Sharia Compliance Audit have a positive effect on Preventive Fraud Efforts. Simultaneously, Supervision, Anti-fraud Strategy, and Sharia Compliance Audit affect Preventive Fraud Efforts.